FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI MASYARAKAT MENGKONVERSI LAHAN SAWIT MENJADI DAERAH PERTAMBANGAN BATU MANGAN DI KENAGARIAN KAMANGKECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Rismawati, Duwi - (STKIP PGRI Sumbar, 2014)
People who convert palm plantation into stone manganese mining area due to the increasing needs of the local economy. This study aims to determine the factors that affect the motivation of people to convert oil palm plantation into stone manganese mining area in kenagarian Kamang kecamatan Kamang baru kabupaten sijunjung, viewed from the level of income, the cost of processing and profits.Type of this research is a descriptive correlational. Population in this study is the patriarch that converts into a palm oil plantation area manganese mining stones in kenagarian kamang kecamatan kamang baru kabupaten sijunjung, totaling 876 patriarchs. Samples were taken with a proportional random sampling technique with a proportion of 10% so that the sample amounted to 76 patriarchs.The results of this study found that: 1) there is the effect on the income level of motivation of people converting oil palm plantation into stone manganese mining area in kenagarian kamang kecamatan kamang baru kabupaten sijunjung with a very small contribution (14,66%). 2) there are significant costs to the processing of the motivation of people to convert oil palm plantation into stone manganese mining area in kenagarian Kamang kecamatan Kamang baru kabupaten Sijunjung with a very small contribution (12,25%). 3) there are significant benefits to society motivational convert oil palm plantation into stone manganese mining area in kenagarian Kamang kecamatan Kamang kabupaten Sijunjung with a very small contribution (16,97%). 4). There is a significant and positive effect of income level, processing costs and profits together to the motivation of society to convert oil palm plantation into stone manganese mining area in kenagarian Kamang kecamatan Kamang kabupaten Sijunjung with a fairly large amount of the contribution, including 41.99%.